ANALYSIS OF LEARNING STYLES AND MATHEMATICAL LITERACY SKILLS OF THE BLIND - Panglipur, Indah Rahayu (STKIP PGRI Situbondo, 2023)
Learning styles for the blind are very important to know. this is to help accuracy in the learning process carried out so that the material can be well received. Likewise, with the ability of the blind master's mathematical literacy, it is important to measure the ability of the blind master to understand material related to mathematics. The purpose of this study was to determine the learning styles and mathematical literacy abilities of the blind. The subjects taken were the blind with the blind type. Qualitative research using observation data collection methods and unstructured interviews. The conclusion is that the learning styles of the blind type are auditory and kinesthetic. While the ability of mathematical literacy is not good because it only meets one indicator of the problem formulation. It needs to be studied further, the same thing for other types of blindness